2018
DOI: 10.1167/18.9.18
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus rivalry and binocular rivalry share a common neural substrate

Abstract: When two incompatible images are shown separately to each eye, a perceptual process known as binocular rivalry occurs by which the two images compete for awareness. The site of competition for binocular rivalry has been a topic of debate, and recent theories are that it may occur either at low levels of the visual system where the inputs from the two eyes are combined or at high levels of the visual system where the two images are processed. One of the major pieces of evidence for a high-level image account of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…Thus, the additional demands of temporal integration in stimulus rivalry did not greatly interact with the demands of spatial integration. Instead, the results were consistent with earlier conclusions that stimulus rivalry is a weaker form of binocular rivalry with shared neural substrates (Buckthought et al 2015 ; Petruk et al 2018 ). Although we acknowledge the relatively low sample size of this study, we have proceeded cautiously with the aim to offer reproducible conclusions.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, the additional demands of temporal integration in stimulus rivalry did not greatly interact with the demands of spatial integration. Instead, the results were consistent with earlier conclusions that stimulus rivalry is a weaker form of binocular rivalry with shared neural substrates (Buckthought et al 2015 ; Petruk et al 2018 ). Although we acknowledge the relatively low sample size of this study, we have proceeded cautiously with the aim to offer reproducible conclusions.…”
Section: Discussionsupporting
confidence: 90%
“…It was thus suggested that stimulus rivalry engages early masking mechanisms that are possibly pre-cortical (Baker and Graf 2009 ; Baker et al 2007 ; Brascamp et al 2013 ). Consistently, Petruk et al ( 2018 ) used SSVEP to show that binocular and stimulus rivalry shared common neural substrates, with an index of competition co-localized in occipital cortex.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations